A Clinicopathologic and Molecular Analysis of Fumarate Hydratase-deficient Renal Cell Carcinoma in 32 Patients. (January 2020) - Lau, Hubert D.; Chan, Emily; Fan, Alice C.; Kunder, Christian A.; Williamson, Sean R.; Zhou, Ming; Idrees, Muhammad T.; Maclean, Fiona M.; Gill, Anthony J.; Kao, Chia-Sui
Abstract : Fumarate hydratase-deficient renal cell carcinoma (FH-deficient RCC) is a rare and recently described entity associated with hereditary leiomyomatosis and RCC syndrome. FH-deficient RCC may show variable clinical and pathologic findings, but commonly presents with locally advanced and metastatic disease and carries a poor prognosis. We identified 32 patients with FH-deficient RCC, confirmed by FH immunohistochemistry (IHC) and/or FH mutation analysis, and performed a retrospective review of the clinical and pathologic features. Median age at presentation was 43 years (range, 18 to 69 y), and the M:F ratio was 2.2:1. Median tumor size was 6.5 cm (range, 2.5 to 28 cm), and 71% presented at stage ≥pT3a. After a median follow-up of 16 months (range, 1 to 118 mo) in 26 patients, 19% showed no evidence of disease, 31% were alive with disease, and 50% were dead of disease. The vast majority of cases showed multiple histologic growth patterns, with papillary (52%) being the most common predominant pattern, followed by solid (21%), cribriform/sieve-like (14%), sarcomatoid (3%), tubular (3%), cystic (3%), and low-grade oncocytic (3%). Viral inclusion-like macronucleoli with perinucleolar clearing were present in almost all cases (96%). All cases were evaluated using FH IHC, and 3 cases (9%) showed retained FH expression. Nineteen cases had germline or tumor mutation analysis confirming a FH mutation, with 79% (11/14) of cases showing mutations within coding regions and 21% (3/14) showing mutations within intronic splice-sites. By IHC, 97% (32/33) of cases were negative for CK7, 93% (27/29) were negative for p63, and 52% (15/29) were negative for GATA3. All cases stained were positive for PAX8 and showed retained succinate dehydrogenase B expression. Our overall findings show that FH-deficient RCC is considerably heterogenous in morphology and frequently behaves aggressively. Suspicion for this entity should be raised even in the absence of predominantly papillary architecture and characteristic nucleolar features. We have included cases with uncommonly seen features, including 4 cases with predominantly cribriform/sieve-like architecture as well as one case with pure low-grade oncocytic morphology (9 y of clinical follow-up without evidence of disease). Although FH IHC is a useful tool for identifying cases of FH-deficient RCC, not all cases of FH-deficient RCC show loss of FH staining, and FH mutation analysis should be considered for patients with suspicious clinical or pathologic features, even in cases with retained FH IHC expression.